2020
DOI: 10.1101/2020.05.12.091660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are mice born normally with an egg-only diet?

Abstract: Chicken eggs (egg) contain high amounts of important proteins and fat with a very low amount of 2 carbohydrates, and also contain all vitamins and minerals needed for the chick to develop. We mated 8-week-old mice consuming an egg-only diet, and examined whether mice got pregnant and mice gave birth. Then we continued to raise newborn mice only consuming an egg-only diet compared to normal chew diet. We found that the rate of pregnancy of the mice consuming an egg-only diet was not different from that of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Thus the egg-only diet is similar to KD, in that both include very little carbohydrate but is distinctly different in its fat and protein content. Our data revealed a steady relationship between the weight of our ND and egg only mice (Figure 1b) (Isobe & Nishio, 2020), which is significantly different from the pattern in mice fed a KD. KD-fed mice develop a distinct metabolic state characterised by weight loss and increased energy expenditure (Douris et al, 2017), while the appearance and activity of our egg-only mice at 20 months of age were similar to those of the ND control.…”
Section: Egg-only Mice Were Healthycontrasting
confidence: 76%
See 4 more Smart Citations
“…Thus the egg-only diet is similar to KD, in that both include very little carbohydrate but is distinctly different in its fat and protein content. Our data revealed a steady relationship between the weight of our ND and egg only mice (Figure 1b) (Isobe & Nishio, 2020), which is significantly different from the pattern in mice fed a KD. KD-fed mice develop a distinct metabolic state characterised by weight loss and increased energy expenditure (Douris et al, 2017), while the appearance and activity of our egg-only mice at 20 months of age were similar to those of the ND control.…”
Section: Egg-only Mice Were Healthycontrasting
confidence: 76%
“…Taken together this data suggested that mice fed only eggs aged normally when compared to ND mice, furthermore, we wanted to evaluate the effects of these diets on reproductive and pup health. To this end we examined the pups nursed by the egg‐only mice and revealed that while these animals could fall pregnant and deliver their pups (Isobe & Nishio, 2020), there were significant changes in the pup's liver metabolism at 2 and 4 weeks of age. It is worth noting that both the pregnant and nursing mice in the egg only group still presented with normal serum glucose levels (Isobe & Nishio, 2020), and that 1‐ and 2‐week old pups were able to obtain decent nutrition from the mother's milk, and then from eggs themselves for 3 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations